Analisa SWOT dalam Strategi Pemasaran Fibre di Pt. Asia Pasific Fiber - Banuara Nadeak (Economic Reviews Journal, 2024)
To maintain its position as the market leader, PT. ASIA PASIFIC FIBER consistently prioritizes quality, competitive pricing, excellent service, and reliability. This is evidenced by the production output in 2022 amounting to 130,224,973 kg, compared to 105,426,746 kg in 2023. Although there was a decrease in monthly production within a year, it did not disrupt the company's productivity and operations. Based on the SWOT analysis, utilizing the Internal Factors Analysis Summary (IFAS), the total value of strengths is 2.6, while the total value of weaknesses is 1.05, resulting in an IFAS Matrix value of 1.55. Meanwhile, the External Factors Analysis Summary (EFAS) indicates a total value of opportunities at 1.50 and a value of threats at 2.00. Thus, the EFAS matrix analysis yields a value of -0.50, placing it in quadrant 2 on the SWOT analysis diagram. Therefore, the recommended strategy is diversification, focusing on enhancing quality and maintaining competitive pricing in the long term, along with establishing long-term partnerships (MOUs) with transportation fleets to ensure timely distribution of goods. The distribution of fiber production involves a safety triangle comprising the Marketing Manager, Production Planner Controller, and Quality Control components, ensuring precise targeting in distribution.